A Maternal High-Fat Diet Causes Anxiety-Related Behaviors by Altering Neuropeptide Y1 Receptor and Hippocampal Volumes in Rat Offspring: the Potential Effect of N-Acetylcysteine - Tüfekci, Kıymet Kübra; Bakirhan, Elfide Gizem; Terzi, Funda (Springer Science and Business Media LLC, 2022)
The children of obese mothers are known to have a high risk of obesity and metabolic disease and are prone to developing cognitive deficits, although the underlying mechanism is not yet fully understood. This study investigated the relationship between neuropeptide Y1 receptor (NPY1R) and anxiety-like behaviors in the hippocampi of male rat offspring exposed to maternal obesity and the potential neuroprotective effects of N-acetylcysteine (NAC). A maternal obesity model was created using a high-fat (60% k/cal) diet. NAC (150 mg/kg) was administered by intragastric gavage for 25 days in both the NAC and obesity + NAC (ObNAC) groups. All male rat offspring were subjected to behavioral testing on postnatal day 28, the end of the experiment. Stereological analysis was performed on hippocampal sections, while NPY1R expression was determined using immunohistochemical methods. Stereological data indicated significant decreases in the total volume of the hippocampus and CA1 and dentate gyrus (DG) regions in the obese (Ob) group (p < 0.01). Decreased NPY1R expression was observed in the Ob group hippocampus (p < 0.01). At behavioral assessments, the Ob group rats exhibited increased anxiety and less social interaction, although the ObNAC group rats exhibited stronger responses than the Ob group (p < 0.01). The study results show that NAC attenuated anxiety-like behaviors and NPY1R expression and also protected hippocampal volume against maternal obesity. The findings indicate that a decrease in NPY1R-positive neurons in the hippocampus of male rats due to maternal conditions may be associated with increased levels of anxiety and a lower hippocampal volume. Additionally, although there is no direct evidence, maintenance of NPY1R expression by NAC may be critical for regulating maternal obesity-induced anxiety-related behaviors and hippocampal structure.
Keywords: Male; Pregnancy in Obesity; Anxiety; Diet, High-Fat; Hippocampus; Rats; Acetylcysteine; Pregnancy; Humans; Animals; Female; Obesity; 2. Zero hunger